Assessing acceptability and identifying barriers and facilitators to implementation of the EULAR recommendations for patient education in inflammatory arthritis: a mixed-methods study with rheumatology professionals in 23 European and Asian countries. Issue 10 (8th June 2022) - Bennett, Sarah E; Zangi, Heidi A; Larsson, Ingrid; Beauvais, Catherine; Boström, Carina; Domján, Andrea; van Eijk-Hustings, Yvonne; Van der Elst, Kristien; Fayet, Françoise; Ferreira, Ricardo J O; Fusama, Mie; Geneva-Popova, Mariela; et al.
Abstract : Objectives: To disseminate and assess the level of acceptability and applicability of the European Alliance of Associations for Rheumatology (EULAR) recommendations for patient education among professionals in rheumatology across Europe and three Asian countries and identify potential barriers and facilitators to their application. Methods: A parallel convergent mixed-methods design with an inductive approach was used. A web-based survey, available in 20 different languages, was distributed to health professionals by non-probability sampling. The level of agreement and applicability of each recommendation was assessed by (0–10) rating scales. Barriers and facilitators to implementation were assessed using free-text responses. Quantitative data were analysed descriptively and qualitative data by content analysis and presented in 16 categories supported by quotes. Results: A total of 1159 completed the survey; 852 (73.5%) were women. Most of the professionals were nurses (n=487), rheumatologists (n=320), physiotherapists (n=158). For all recommendations, the level of agreement was high but applicability was lower. The four most common barriers to application were lack of time, lack of training in how to provide patient education, not having enough staff to perform this task and lack of evaluation tools. The most common facilitators were tailoring patient education to individual patients, using group education, linking patient education with diagnosis and treatment and inviting patients to provide feedback on patient education delivery. Conclusions: This project has disseminated the EULAR recommendations for patient education to health professionals across 23 countries. Potential barriers to their application were identified and some are amenable to change, namely training patient education providers and developing evaluation tools.